Sistem Penerimaan Part Berbasis Website Di Pt. Indonesia Epson Industry Kawasan Ejip Cikarang - Arif Susilo; Yoga Purnomo (Prosiding Sains dan Teknologi, 2025)
The development of information system requirements is crucial in all activities, especially in business operations, where efficient management is essential to achieve company goals. PT Indonesia Epson Industry, a printer manufacturing company, currently handles warehouse part reception manually. This manual process makes it time-consuming to locate missing parts and can potentially cause production line stoppages, affecting overall productivity. To address these issues, a part reception information system has been developed. The system is built using PHP with the CodeIgniter framework and MySQL database to manage and monitor warehouse data effectively. With this system, all part information, including location, delivery status, and related details, can be accessed digitally. When a part is missing or needs verification, warehouse admins can quickly check the system to obtain accurate and up-to-date information, eliminating delays caused by manual tracking. This approach streamlines warehouse operations, reduces the risk of part loss, and ensures smoother production processes. By implementing this computerized system, PT Indonesia Epson Industry can enhance operational efficiency, improve monitoring capabilities, and maintain production continuity while minimizing disruptions in the warehouse workflow.